Protective effect of Diadema setosum gonad extract against oxidative stress in D-Galactose-induced aging rats - Arlina Wiyata Gama; Suryani As'ad; Gemini Alam; Athirah Rinandha Eragradini (AcTion: Aceh Nutrition Journal, 2025)
Oxidative stress is a primary mechanism of aging and is characterized by elevated levels of malondialdehyde (MDA). Natural antioxidants are being increasingly explored for the prevention of premature aging. The gonads of the sea urchin Diadema setosum contain bioactive compounds, including omega-3 fatty acids, flavonoids, and phenolics, which possess unique ecological adaptations that enhance secondary metabolite production, making them a promising marine antioxidant source. This study aimed to evaluate the effect of D. setosum gonad extract on MDA levels in male Wistar rats undergoing d-galactose-induced aging. An experimental post-test control group design was conducted from July to November 2024, involving 24 rats divided into four groups: standard control (K1), positive control (K2), and two treatment groups receiving extracts at doses of 100 mg/kg (P1) and 300 mg/kg (P2). D-galactose was used for aging at 150 mg/kg body weight for eight weeks, followed by oral administration of the extract for an additional eight weeks. MDA levels were measured using ELISA at weeks 0, 6, 10, and 14. The results showed a significant increase in MDA levels in the positive control group (K2) compared to the normal group (p=0.002), indicating oxidative stress induction. In contrast, treatment with D. setosum gonad extract, particularly in the P2 group, significantly reduced MDA levels (p<0.05), approaching those of the normal group. In conclusion, D. setosum gonad extract has potential as a natural antioxidant for suppressing oxidative stress associated with aging.